Social Values and Determinants of Cultural Fit in Quebec: The Roles of Ancestry, Linguistic Group, and Mental Health Status - Crafa, Daina; Liu, Joanna Q.; Brodeur, Mathieu B. (Frontiers in Psychology, 2019)
Many quantitative research studies assume that cultural groups consist of anyone born and raised in the same country. Applying these criteria to the formation of study samples may produce cohorts that share a country but that are heterogeneous in relevant domains of culture. For example, in Canada, Franco- and Anglo-Canadians are generally assumed to represent different linguistic groups but the same cultural group. However, speaking a different first language also can mean exposure to different media, information, and conventions, which are known to shape certain cultural domains, such as social values. Other factors may produce cultural heterogeneity. For example, ancestral origins and recency of familial migration may influence endorsed social values after exposure to diverse cultures or norms. Mental health status or psychiatric conditions may also influence subscription of social values due to different lifestyle demands. Understanding the nuanced contributions of diverse backgrounds to cultural membership and fit (i.e., the degree to which an individual behaves like other cultural members) is useful when performing quantitative cross-cultural studies to minimize alternative explanations for statistical outcomes. This study used Cultural Consensus Analysis (CCA) to assess the cultural fit of social values for 222 Canadians who had participated in neuropsychological experiments. CCA is an anthropological statistical method for evaluating cultural agreement. Participants were systematically evaluated by linguistic group (French, English), migratory generation (1st-3rd+), and mental health status (healthy, patient). Group and individual variances were statistically interrogated. Results demonstrated that Franco- and Anglo-Canadians represent different cultural groups cohabitating in Quebec. Social values dividing Franco- and Anglo-Canadians were identified. Second and third generation Canadians held more heterogeneous social values than Canadians whose families had migrated earlier. Second generation Canadians with psychiatric disorders showed notably reduced cultural fit with other Canadians, which supports other literature reporting difficulties experienced by second-generation migrants. However, third and later generations of Canadians with psychiatric disorders held greater ranges of social values compared to healthy Canadians but were good fits for Canadian culture. This study concludes that linguistic group and migratory generation partially determine cultural group in the social values domain while mental health status does not, contrary to previous theories.